Public health research outputs from efficacy to dissemination: a bibliometric analysis - Milat Andrew J (BMC Public Health, 2011)
Abstract Background More intervention research is needed, particularly 'real world' intervention replication and dissemination studies, to optimize improvements in health. This study assessed the proportion and type of published public health intervention research papers over time in physical activity and falls prevention, both important contributors to preventable morbidity and mortality. Methods A keyword search was conducted, using Medline and PsycINFO to locate publications in 1988-1989, 1998-1999, and 2008-2009 for the two topic areas. In stage 1, a random sample of 1200 publications per time period for both topics were categorized as: non-public health, non-data-based public health, or data-based public health. In stage 2 data-based public health articles were further classified as measurement, descriptive, etiological or intervention research. Finally, intervention papers were categorized as: efficacy, intervention replication or dissemination studies. Inter-rater reliability of paper classification was 88%. Results Descriptive studies were the most common data-based papers across all time periods (1988-89; 1998-1999;2008-2009) for both issues (physical activity: 47%; 54%; 65% and falls 75%; 64%; 63%), increasing significantly over time for physical activity. The proportion of intervention publications did not increase over time for physical activity comprising 23% across all time periods and fluctuated for falls across the time periods (10%; 21%; 17%). The proportion of intervention articles that were replication studies increased over the three time periods for physical activity (0%; 2%; 11%) and for falls (0%; 22%; 35%). Dissemination studies first appeared in the literature in 2008-2009, making up only 3% of physical activity and 7% of falls intervention studies. Conclusions Intervention research studies remain only a modest proportion of all published studies in physical activity and falls prevention; the majority of the intervention studies, are efficacy studies although there is growing evidence of a move towards replication and dissemination studies, which may have greater potential for improving population health.